A methodology for estimating accurate velocity field of NigNET based on new ITRF realization - BAWA, Swafiyudeen; OJIGI, Lazarus Mustapha; DODO, Joseph Danasabe; LAWAL, Kola Muideen (Contributions to Geophysics and Geodesy, 2022)
This contribution presents a new velocity field describing the crustal motion of Nigeria from more than 5years continuous GNSS data at 8 of 14 permanent stations distributed across the country. GAMIT/GLOBK GNSS processing software was used for processing. The horizontal velocity field of NigNET stations which showed a North-East trend and the selected IGS stations were obtained from cleaned position time series of daily GNSS solutions. The velocity describe the horizontal and vertical motion the selected 8 GNSS stations assuming Flicker +White noise model, which optimally describes the geophysical error source of the adopted GNSS stations. Bland and Altman statistical method shows that residual velocity solutions of our study and others (in ITRF2008) and also MORVEL plate motion model are in agreement.